2023
DOI: 10.1111/jir.13027
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physical fitness and cardiovascular disease in older adults with intellectual disabilities: Results of the Healthy Ageing and Intellectual Disability study

Abstract: Background Reduced physical fitness is a cardiovascular disease (CVD) risk factor in the general population. However, generalising these results to older adults with intellectual disabilities (ID) may be inappropriate given their pre-existing low physical fitness levels and high prevalence of comorbidities. Therefore, the aim of this study is to investigate the difference in physical fitness between older adults with ID with and without CVD. Method Baseline data of a cohort of older adults with borderline to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A study conducted by the Journal of Intellectual Disability Research confirmed that adults with intellectual disabilities have low physical fitness levels. However, this study is conducted to inquire about the physical ability of people with intellectual disabilities, not how the physical disability relates to intellectual disability [10]. Two other researchers also inquired about the benefits of physical activities to adults with intellectual disabilities, and the study was conducted on adults and physical activities [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by the Journal of Intellectual Disability Research confirmed that adults with intellectual disabilities have low physical fitness levels. However, this study is conducted to inquire about the physical ability of people with intellectual disabilities, not how the physical disability relates to intellectual disability [10]. Two other researchers also inquired about the benefits of physical activities to adults with intellectual disabilities, and the study was conducted on adults and physical activities [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%